KNOWLEDGE FEATURES ОF JOURNALISM PUBLICISM OF SAMCHUK ULAS - Хороб, C. C. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article makes an attempt to define genre peculiarities of the open journalism by a writer from the Ukrainian diaspora on the material of Ulas Samchuk’s journalistic publications in the period of wartime and after-war years (1938-1948). It proves that, having his articles published in different periodicals, the prosaic and journalist often used such forms as the analytical correspondence, the reportage, the essay, the feuilleton, etc. In addition, it outlines the connection between the fictional and open journalistic creative work by the known master of the word, takes into consideration the researches into this problem by emigre and continental national scholars.